Lagu Marsinondang Dibaen Jesus Karya Philip Paul Bliss: Analisis Bentuk dan Makna Lagu - Emmi Simangunsong; Ance Juliet Panggabean; Ronald Heriko Saragih; Eston Hernandes P. (Universitas Negeri Medan, 2025)
This study aims to analyze the form and meaning of the song Marsinondang Dibaen Jesus from the Ende HKBP book number 518 by Philip Paul Bliss. The song is sung by the congregation during Sunday services at the HKBP Church and other services. The song was composed by Philip after hearing a sermon from Dwight Lyman Moody about a storm that occurred at the Cleveland harbor docks which had two lighthouses, called the upper light and the lower light. The captain couldn't see the lower lights, which caused the ship to sink to the bottom of the sea. Only a small number of the crew survived, and most drowned. Based on Moody's account, Philip wrote the song